Fungal biofilms as a valuable target for the discovery of natural products that cope with the resistance of medically important fungi—Latest findings - Butassi, Estefanía (2021)
The development of new antifungal agents that target biofilms is an urgent need. Natural products, mainly from the plant kingdom, represent an invaluable source of these entities. The present review provides an update (2017–May 2021) on the available information on essential oils, propolis, extracts from plants, algae, lichens and microorganisms, compounds from different natural sources and nanosystems containing natural products with the capacity to in vitro or in vivo modulate fungal biofilms. The search yielded 42 articles; seven involved essential oils, two Brazilian propolis, six plant extracts and one of each, extracts from lichens and algae/cyanobacteria. Twenty articles deal with the antibiofilm effect of pure natural compounds, with 10 of them including studies of the mechanism of action and five dealing with natural compounds included in nanosystems. Thirty‐seven manuscripts evaluated Candida spp. biofilms and two tested Fusarium and Cryptococcus spp. Only one manuscript involved Aspergillus fumigatus. From the data presented here, it is clear that the search of natural products with activity against fungal biofilms has been a highly active area of research in recent years. However, it also reveals the necessity of deepening the studies by (i) evaluating the effect of natural products on biofilms formed by the newly emerged and worrisome health‐care associated fungi, C. auris, as well as on other non‐albicans Candida spp., Cryptococcus sp. and filamentous fungi; (ii) elucidating the mechanisms of action of the most active natural products; (iii) increasing the in vivo testing.